2014
DOI: 10.1146/annurev-cellbio-100913-013053
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Regulation of Synaptic Behavior

Abstract: Astrocytes regulate multiple aspects of neuronal and synaptic function from development through to adulthood. Instead of addressing each function independently, this review provides a comprehensive overview of the different ways astrocytes modulate neuronal synaptic function throughout life, with a particular focus on recent findings in each area. It includes the emerging functions of astrocytes, such as a role in synapse formation, as well as more established roles, including the uptake and recycling of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
216
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 264 publications
(220 citation statements)
references
References 147 publications
3
216
0
1
Order By: Relevance
“…Work over the past decade has overwhelmingly demonstrated that astrocytes, which were once thought to function only as supporting cells for neurons, play diverse and essential regulatory roles in the developing and adult CNS (reviewed by Allen, 2014). Astrocytes are the most abundant cell type in the vertebrate CNS, and are classified as protoplasmic (gray matter) or fibrous (white matter).…”
Section: Roles Of Astrocytes In Cns Development and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work over the past decade has overwhelmingly demonstrated that astrocytes, which were once thought to function only as supporting cells for neurons, play diverse and essential regulatory roles in the developing and adult CNS (reviewed by Allen, 2014). Astrocytes are the most abundant cell type in the vertebrate CNS, and are classified as protoplasmic (gray matter) or fibrous (white matter).…”
Section: Roles Of Astrocytes In Cns Development and Functionmentioning
confidence: 99%
“…More recently, it has become apparent that astrocytes also powerfully control the formation, strength and turnover of synapses. Since the first demonstrations nearly two decades ago that astrocytes are required for the formation of functional synapses in retinal ganglion cells, there has been great progress in identifying the numerous proteins released by astrocytes that control excitatory synapse formation and function (reviewed by Clarke and Barres, 2013;Allen, 2014). These include astrocytesecreted proteins that trigger the formation of postsynaptically silent synapses (e.g.…”
Section: Roles Of Astrocytes In Cns Development and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional significance of this is unclear, but to the extent that glial sheaths control transmitter availability [e.g., (3,118)], such a process would be absent in glomeruli. A final point is that synapses from interneuronal axons are also often found in glomeruli, but these make conventional, simple synapses, unlike their dendritic counterparts.…”
Section: Thalamic Circuit Propertiesmentioning
confidence: 99%
“…Much of this has to do with the modulator properties of this pathway and its ability to activate metabotropic glutamate receptors. At least four independent sites of action of the pathway have so far been demonstrated, and these are outlined in Figure 9 [1] The IPSP activated indirectly in thalamic relay cells via the local GABAergic cells tends to be larger than and can swamp the direct EPSP (85); [2] cortical activation of presynaptic metabotropic glutamate receptors on retinal terminals reduces transmitter release and thus the gain of retinogeniculate transmission (51,86); [3] layer 6 input onto thalamocortical target cells in layer 4 often produces sustained hyperpolarization through activation of postsynaptic group II metabotropic glutamate receptors (90); and [4] layer 6 input to layer 4 cells activates metabotropic glutamate receptors presynaptically on thalamocortical terminals to reduce transmitter release and down regulate thalamocortical EPSPs (92). Note that each of these actions would result in a reduction of the gain of thalamocortical transmission, and in this regard, it is more consistent with the recent demonstration that reaches a similar conclusion from optogenetic control of the pathway (115).…”
Section: The Layer 6 Corticothalamic Pathwaymentioning
confidence: 99%